2020
DOI: 10.1007/s00216-020-02490-2
|View full text |Cite
|
Sign up to set email alerts
|

PCR inhibition in qPCR, dPCR and MPS—mechanisms and solutions

Abstract: DNA analysis has seen an incredible development in terms of instrumentation, assays and applications over the last years. Massively parallel sequencing (MPS) and digital PCR are now broadly applied in research and diagnostics, and quantitative PCR is used for more and more practises. All these techniques are based on in vitro DNA polymerization and fluorescence measurements. A major limitation for successful analysis is the various sample-related substances that interfere with the analysis, i.e. PCR inhibitors… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
103
0
3

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 186 publications
(134 citation statements)
references
References 140 publications
0
103
0
3
Order By: Relevance
“…Our optimised protocol uses phenol/chloroform (1:1, v/v) followed by a second clean up with QIAGEN affinity column. Although a second clean up may not be necessary, based on the low recovery of ChIP and potential interference of carbohydrates, polysaccharides, and phenol in inhibiting library amplification [57] it would be ideal to use a column clean product prior to library preparation. Silica membrane spin columns are recommended to remove carbohydrates and polysaccharides.…”
Section: Discussionmentioning
confidence: 99%
“…Our optimised protocol uses phenol/chloroform (1:1, v/v) followed by a second clean up with QIAGEN affinity column. Although a second clean up may not be necessary, based on the low recovery of ChIP and potential interference of carbohydrates, polysaccharides, and phenol in inhibiting library amplification [57] it would be ideal to use a column clean product prior to library preparation. Silica membrane spin columns are recommended to remove carbohydrates and polysaccharides.…”
Section: Discussionmentioning
confidence: 99%
“…Successful amplification using direct PCR or direct LAMP, in which small volumes of unprocessed sample are added to the DNA amplification reactions, has demonstrated that some sample types do not require processing before amplification 26,27 . These methods do not involve nucleic acid purification but rather rely on the capability of DNA polymerases to tolerate low levels of contaminants in the reactions 28 . By contrast, the dipstick method presented here actively removes DNA amplification inhibitors before elution, as demonstrated in experiments in which samples added directly into DNA amplification reactions failed to amplify, whereas dipstick purifications from the same samples resulted in the successful amplification 5 .…”
Section: Comparison With Other Methodsmentioning
confidence: 99%
“…Despite the great diagnostic potential of PCR, the success of each of its practical applications is highly dependent on the quality of samples containing nucleic acids for amplification. The spectrum of different inhibitors of PCR complicating the work in real-world samples, such as false-negative results or higher limits of detection, have been characterized [ 60 ]. Procedures leading to sufficient purification of samples [ 61 , 62 ] and to the development of inhibition-resistant DNA polymerases [ 63 ] have been developed.…”
Section: Outstanding Challenges In Pcrmentioning
confidence: 99%
“…Procedures leading to sufficient purification of samples [ 61 , 62 ] and to the development of inhibition-resistant DNA polymerases [ 63 ] have been developed. It has been documented that dPCR is more resistant to the presence of inhibitors [ 60 ].…”
Section: Outstanding Challenges In Pcrmentioning
confidence: 99%